The Dead Sea scrolls and contemporary culture : proceedings of the international conference held at the Israel Museum, Jerusalem (July 6-8, 2008) - Roitman, Adolfo Daniel.; Schiffman, Lawrence H.; Tzoref, Shani. (Studies on the Texts of the Desert of Judah, 2011)
This volume contains the proceedings of the international conference held at the Israel Museum in Jerusalem in July 2008 in honor of the 60th anniversary of the discovery of the Dead Sea Scrolls. As indicated by its title "The Dead Sea Scrolls and Contemporary Culture," the aim of the conference was to move beyond the strict confines of conventional scholarship and to explore new avenues of research, including the examination of the place of the findings from the Judean Desert in contemporary culture. The book is divided into five main sections: (1) the Identity and History of the Community; (2) the Qumran "Library": Origins, Use, and Nature (2a. Biblical Texts; 2b. Biblical Interpretation; 2c. Sectarian and Non-Sectarian Literature; 2d. Sectarian vis-à-vis Rabbinic Halakha); (3) Christianity in Light of the Dead Sea Scrolls; (4) Gender at Qumran; and (5) New Perspectives (5a. Methodological Approaches; 5b. Educational Approaches).